IMPROVING THE DIGITAL MANAGEMENT SYSTEM IN CULTURAL AND ART INSTITUTIONS IN UZBEKISTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article analyzes the necessity and benefits of improving the digital management system in Uzbekistan’s cultural and art institutions. It examines how the introduction of digital systems can enhance operational efficiency, transparency, and financial effectiveness within these institutions. Additionally, the article explores the challenges encountered in this transformation and the potential solutions.